2007
DOI: 10.1179/146532807x192480
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate use of empirical antibiotics in acute diarrhoea: a cross-sectional survey in southern Thailand

Abstract: Overuse of antibiotics in the treatment of acute diarrhoea in children is common. The prevalence differs between different levels of hospitals and different types of medical personnel. Physicians might mistake some patients' clinical features of diarrhoea as features of dysentery, leading to unnecessary prescription of antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 11 publications
4
14
2
Order By: Relevance
“…The lowest rate of antibiotic prescription seen in this study was for diarrheal illnesses being 50%. This is higher than that observed by some, where 44% of diarrheal illnesses received antibiotics, but much lower than over 70% reported by some investigators [23,24].…”
Section: Original Research Articlecontrasting
confidence: 59%
“…The lowest rate of antibiotic prescription seen in this study was for diarrheal illnesses being 50%. This is higher than that observed by some, where 44% of diarrheal illnesses received antibiotics, but much lower than over 70% reported by some investigators [23,24].…”
Section: Original Research Articlecontrasting
confidence: 59%
“…A study conducted in Peru [23] revealed that the physicians' prescribing practices of antimicrobials seemed to be more related to agreement with social expectations rather than their knowledge and guidelines. A cross-sectional survey conducted in Thailand also showed an overuse of antibiotics in the treatment of acute diarrhea [24].…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies [17][18][19] conducted in other countries mainly for children that have shown frequent prescription of antibiotics for the treatment of acute diarrhea.…”
Section: Discussionmentioning
confidence: 99%